Pengaruh Model Project Based Learning (PjBL) terhadap Kemampuan Pemecahan Masalah pada Materi Penyajian Data di Kelas V SD - Asna Mardin; Melva Zainil (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
This research is motivated by presence of mathematical problem in life, to develop someone's ability to deal with a problem. Therefore problem solving skills are the main focus in mathematics learning. This study aims to determine the effect of using PjBL model on students' problem solving abilities. This type of research is Quasi Experimental. The technique of the sampling is using cluster random sampling. The instrument used is an Essay test. Based on the calculation of the results analysis, t-test with a significance level of 0.05 obtained t-count (11.3363) and t-table (2.162). So that t-count > t-table, where 11,363> 2,162. Ha is accepted, it can be concluded that there is the effect of using the PjBL model on problem solving skills in data presentation material of fifth grade students of SD Gugus IV Kecamatan Padang Utara. Keywords: Project Based Learning, Problem Solving Skills